2017
DOI: 10.21273/hortsci12291-17
|View full text |Cite
|
Sign up to set email alerts
|

Winter Broccoli and Cauliflower under Organic High Tunnels in a Humid, Subtropical Climate

Abstract: Abstract. There is a lack of information related to adapting high tunnel systems to humid, subtropical climates in the Southeastern United States, resulting in a disadvantage for their use to extend growing seasons and meet the increasing demand for local horticulture products. This research project explored the possibility of growing organic broccoli and cauliflower (Brassica oleracea L.) under high tunnels during two consecutive fall/winter seasons in northeast Georgia (USDA plant hardiness zone 8a), particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…In 2015, the mini-lettuce yield (i.e., mean marketable head weight) was similar between the high tunnels and the field, but in 2016, the yield was greater under the high tunnels. Our results are similar to other studies that have found high tunnels can boost yields but that biotic or abiotic variables can affect crop yields in any given year (Jayalath et al, 2017;O'Connell and Tate, 2017;O'Connell et al, 2012;Rho et al, 2020;Wallace et al, 2012). It is unclear why the high tunnel system had yield increases in 2016, while overall the field system had yield decreases compared with 2015.…”
Section: Discussionsupporting
confidence: 84%
“…In 2015, the mini-lettuce yield (i.e., mean marketable head weight) was similar between the high tunnels and the field, but in 2016, the yield was greater under the high tunnels. Our results are similar to other studies that have found high tunnels can boost yields but that biotic or abiotic variables can affect crop yields in any given year (Jayalath et al, 2017;O'Connell and Tate, 2017;O'Connell et al, 2012;Rho et al, 2020;Wallace et al, 2012). It is unclear why the high tunnel system had yield increases in 2016, while overall the field system had yield decreases compared with 2015.…”
Section: Discussionsupporting
confidence: 84%
“…In is also noteworthy that the non-shaded high tunnel had a reduction in PPFD of 30.3% compared to outdoor ambient conditions. Other studies have reported similar effects of plastic deterioration on shading in high tunnels [22]. The combination of shading from both plastic and the shade cloth, resulting in a reduction in PPFD of 51% in the shaded high tunnel compared to outdoor conditions.…”
Section: Discussionsupporting
confidence: 51%
“…Although well documented for use in greenhouses, less information is available evaluating the effectiveness of shade cloth and fogging/misting systems in passively cooled structures such as high tunnels in hot humid climates, such as the Southeastern United States, is limited. Research is needed to develop cultural practices that can be used to mitigate heat stress, which often limits production in regions of the world with similar climates to the Southeastern United States [22]. The objectives of this study were to determine the impact of fogging systems and shade cloth on high tunnel microclimates and growth of fall planted, high tunnel-grown basil, lettuce, and arugula.…”
Section: Introductionmentioning
confidence: 99%
“…Broccoli and cauliflower are not native plants in Indonesia, but are widely cultivated and widely consumed by people in Indonesia. Broccoli and cauliflower are harvested at 7 weeks to 8 weeks after planted 5 . Several analytical methods have been discovered for analysis of Nitrite and Nitrate, such as high performance liquid chromatography 6 and spectrophotometric 7 .…”
Section: Introductionmentioning
confidence: 99%